Metabolic syndrome and spatial disparities: The role of socioeconomic deprivation and medical resource availability in the Cijin district, Taiwan - Pei‐Hung Su; Jong‐Rung Tsai; Wei‐Lun Chang; Hui‐Min Hsieh (Kaohsiung Journal of Medical Sciences)
Abstract Metabolic syndrome (MetS) is a global health concern with spatial disparities, especially in disadvantaged neighborhoods. This study aimed to examine the association between area‐level socioeconomic deprivation, the availability of medical resources in disadvantaged areas such as the Cijin district, and the prevalence of MetS in Taiwan. We used two representative secondary cross‐sectional datasets, including physical examinations and lifestyle surveys from 2016 to 2020, sourced from the Taiwan Biobank and the Cijin District Adult Lifestyle and Health Survey. Our findings indicate that residing in the Cijin district, characterized by socioeconomic deprivation and limited medical resources, is associated with significantly higher odds of MetS (aOR = 1.45, 95% CI = 1.28–1.64, p <0.001). Additionally, living in areas with medium (aOR = 1.12, 95% CI = 1.07–1.17, p <0.001) and high area‐level socioeconomic deprivation indexes (aOR = 1.13, 95% CI = 1.01–1.25, p <0.001) is linked to a higher likelihood of MetS. Conversely, residing in high medical resource availability index areas is associated with a lower risk of MetS (aOR = 0.92, 95% CI = 0.86–0.99, p = 0.026). We found a link between socioeconomic deprivation and limited medical resources, especially in disadvantaged areas such as the Cijin district, contributing to a higher MetS risk. Residents in these areas often struggle to access healthcare and preventive care. Addressing these disparities requires comprehensive public health initiatives and targeted policy interventions to improve residents' well‐being.